2022
DOI: 10.3390/jfmk7010009
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Body Tempering on Force Production, Flexibility and Muscle Soreness in Collegiate Football Athletes

Abstract: There has been limited research to explore the use of body tempering and when the use of this modality would be most appropriate. This study aimed to determine if a body tempering intervention would be appropriate pre-exercise by examining its effects on perceived soreness, range of motion (ROM), and force production compared to an intervention of traditional stretching. The subjects for this study were ten Division 1 (D1) football linemen from Sacred Heart University (Age: 19.9 ± 1.5 years, body mass: 130.9 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
0
0
Order By: Relevance
“…The study revealed that athletes who performed SMR exercises after football training sessions had better perceived recovery and less feeling of tiredness 24 h after the exertion during training, compared to those athletes performing a passive recovery. This statement has been supported by other studies of the athlete population, which applied co-pressure methodologies in potentiation and recovery, finding positive results in the reduction in delayed pain [104]. In the same spirit, Rahimi et al [72] reported better recovery results (lower HI scores) for the FR group compared to a passive rest group, especially on the second and third match days.…”
Section: Discussionmentioning
confidence: 61%
“…The study revealed that athletes who performed SMR exercises after football training sessions had better perceived recovery and less feeling of tiredness 24 h after the exertion during training, compared to those athletes performing a passive recovery. This statement has been supported by other studies of the athlete population, which applied co-pressure methodologies in potentiation and recovery, finding positive results in the reduction in delayed pain [104]. In the same spirit, Rahimi et al [72] reported better recovery results (lower HI scores) for the FR group compared to a passive rest group, especially on the second and third match days.…”
Section: Discussionmentioning
confidence: 61%
“…Neural/psychological outcomes including perceived pain [57, 99,187,251,292,304], soreness [139,245,277,278,286,320,324], and exertion [174, 203-205, 245, 248, 264, 287, 315, 349, 353] were the most commonly reported outcomes in this context, but other outcomes were considered as well (e.g., mood state [245,347]).…”
Section: Main Outcomes Assessed Per Domainmentioning
confidence: 99%